Expert Evidence and Assessments in Child Welfare Cases - Bala, Nicholas; Thomson, Jane (Social Science Research Network, 2015)
Expert evidence from mental health professionals and medical doctors can play a central role in child welfare cases, and this evidence needs to be carefully scrutinized before it is relied upon in making critical decisions about the future of parent-child relationships. In Ontario, concern about the reliability of expert evidence in child abuse and neglect cases was heightened by the 2014 decision of the Court of Appeal in R v. Broomfield, where a mother’s conviction on criminal charges related to giving her infant child cocaine based on testimony by an expert from the Motherisk Drug Testing Lab at the Toronto Hospital for Sick Children. In overturning the conviction, the Court of Appeal noted that “the trial judge made her decision unaware of the genuine controversy among the experts about the use of the testing methods relied upon by the Crown expert at trial to found a conclusion of chronic cocaine ingestion.” In the months following the Court of Appeal decision in Broomfield, the Attorney General of Ontario appointed a former justice of the Court of Appeal, Susan Lang, to undertake a Review to assess the adequacy and reliability of hair analysis evidence used in child protection and criminal proceedings (report to be released Dec. 15, 2015).